Различия в восприятии цветовых эталонов в польском и русском языках - Narloch, Andrzej (Studia Rossica Posnaniensia, 2014)
The author of the article tries to present the semantic differences in the perception of color patterns based on the example of two languages – Polish and Russian. Contemporary dictionaries as well as the psycholinguistic experiment that was conducted among Polish and Russian respondents provided a basis for the research. The author demonstrates the conceptual diversity of ways in which colors are perceived in the two languages. The differences in color semantics that are presented here are determined by different color patterns, different stages of the development of the color pattern and different perceptions of colors in these languages. It is difficult to classify some of the names of dominant colors. Neither do the respondents provide explicit answers, which makes it difficult to precisely define the name of a given color.